Robot Lego, ChatGPT in Scratch kot orodja za učenje matematike v 8. razredu - Nemec, Andrej (Revija inovativna pedagogika, 2025)
In this paper, we want to present an innovative use of the Lego Mindstorms robot, the language model ChatGPT, and the coding tools Scratch and Python in implementing a cross-curricular lesson where we combined robotics and maths together with a maths teacher. Our topic was percentage calculus and its derivatives (percentages, shares, and totals) and the use of a robot as a digital tool in learning mathematical formulas, as we used it to measure certain input data. We tested the theory of the learning material in the artificial intelligence tool ChatGPT and discussed its advantages and disadvantages. The mathematical formulas for calculating percentages were coded in Scratch and Python. In this way, we addressed the importance of input data and the dependency of output data in a computer program. In parallel, we learned about the meaning of a variable in the program and compared the different values that resulted from the operation of the computer program. In this way, the pupils were able to understand and learn mathematical concepts more quickly and relate them to everyday life in a practical way, reinforcing digital skills such as problem-solving, programming, and using technology for learning and acquiring basic computer science skills. This paper is aimed at all mathematics and science teachers and other educational practitioners who want to integrate seemingly disparate content through a multi-faceted approach for more active learning in the classroom.
Keywords: basic skills of computer science; ChatGPT (klepetalni robot); coding; Informacijsko-komunikacijska tehnologija; input and output data; Interdisciplinarnost v izobraževanju; Matematika; Osnovnošolsko izobraževanje; programiranje; robotics; robotika; Scratch (programski jezik); temeljna znanja RIN; vhodni in izhodni podatki